Dampak Zakat terhadap Kemiskinan dan Kesejahteraan Mustahik (Kasus : BAZNAS Provinsi Jawa Tengah) - Isro'iyatul Mubarokah; Irfan Syauqi Beik; Tony Irawan (AL-MUZARA'AH, 2017)
Poverty is one of Indonesia's problems. One of the instruments used to reduce poverty is zakat. This study aims to analyze the impact of zakat on poverty and welfare of mustahik. The method used in this research is the interview with the questionnaire. The method of the sampling used purposive. The analysis tool used CIBEST model. The results show that the index value of Islamic poverty without and with zakat has not changed.